APPLICATION OF THE THEORY OF FANTASTIC WORLDS TO ISAAC ASIMOV’S “THE BICENTENNIAL MAN” - Akhmedov, Rafael (Журнал иностранных языков и лингвистики, 2021)
This article is aimed to reveal how smoothly and accurately the theory and classification of textual worlds, adopted in cognitive poetics, fits the fantastic world created by famous American science fiction writer Isaac Asimov on the pages of his novelette “The Bicentennial Man”.